2014
DOI: 10.1017/s1759078714000786
|View full text |Cite
|
Sign up to set email alerts
|

Substrate-perforated and compact ultra-wideband antenna with WLAN band rejection

Abstract: This paper presents a designed notched band ultra-wideband (UWB) printed antenna using coplanar waveguide-fed configuration. Simple technique of perforating the substrate and modifying the ground plane and radiator patch was used to achieve UWB for the designed antenna at smaller structure. Narrow arch-shaped slot was introduced to the patch of the proposed antenna to obtain the band rejection function around the 5.4 GHz frequency to avoid the interference with WLAN applications. The proposed antenna was fabri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…At a higher frequency, the radiation patterns still retain excellent omnidirectional curves on the H-plane, whereas, a low distortion can be observed for the E plane at 10 GHz. It can be observed that the realized gain of the proposed slotted UWB antenna drop dramatically at the band-notched frequency and have reasonable values away from outwards that are better than the ones achieved in [13][14][15][16]. Furthermore, except at the notched-band a good radiation efficiency is achieved; that is almost over 90 % on the whole working bandwidth of the proposed antenna as depicted in the Fig.…”
Section: Resultsmentioning
confidence: 74%
“…At a higher frequency, the radiation patterns still retain excellent omnidirectional curves on the H-plane, whereas, a low distortion can be observed for the E plane at 10 GHz. It can be observed that the realized gain of the proposed slotted UWB antenna drop dramatically at the band-notched frequency and have reasonable values away from outwards that are better than the ones achieved in [13][14][15][16]. Furthermore, except at the notched-band a good radiation efficiency is achieved; that is almost over 90 % on the whole working bandwidth of the proposed antenna as depicted in the Fig.…”
Section: Resultsmentioning
confidence: 74%